Elucidating the Prognostic Role of BRAFV600E and the Activation Status of the Downstream MAPK Pathway in PTC: A Study from a Tertiary Centre in India - Nadeem Kocheri; Priti Chatterjee; Shipra Agarwal; Mehar C. Sharma; Sanjana Ballal; Chandrasekhar Bal; Sunil Chumber (Indian Journal of Endocrinology and Metabolism)
Introduction: Papillary thyroid carcinoma (PTC) has an excellent prognosis, but few cases are treatment-resistant. To check the applicability of combined BRAFV600E and MEK-targeted therapy, the current study correlated BRAFV600E with the MAPK pathway activation status in a cohort of PTCs. The prognostic relevance of BRAFV600E and the usability of immunohistochemistry (IHC) for detecting the mutation were also assessed. Methods: Randomly selected 50 PTC and 15 non-PTC cases were re-classified according to the 2022 WHO classification. The BRAF mutation status was compared with the IHC of BRAFV600E, pERK1/2, pMEK1/2, and clinicopathological variables, including response to radioactive iodine and disease-free survival. Results: BRAFV600E mutation was present in 38%. Most (87.8%) cases were immunopositive for pMEK1/2 and 40% for pMEK1/2. Although BRAFV600E mutation did not correlate with the MAPK activation status, it had an adverse impact on tumour sensitivity to radioiodine (P < 0.05). Five of the seven radioiodine-resistant tumours were BRAFV600E-mutated. An Allred cut-off score of 7 had a sensitivity of 100% and a specificity of 84% for detecting the mutation by IHC. All the non-PTC cases were BRAF-wild type, but 20% showed weak immunopositivity for mutated protein and were scored 6. Conclusions: BRAFV600E-mutated PTCs are more likely to be RAI-resistant. MAPK pathway activation status did not vary significantly with BRAF mutation. Immunopositivity for pMEK1/2 in most suggests a scope for MEK1-targeted therapy in recalcitrant PTC cases even in the absence of the BRAF mutation. In addition, IHC is a reliable technique for detecting BRAFV600E mutation but needs validation by correlation with molecular studies.